Trade-off between cellular immunity and life span in mealworm beetles Tenebrio molitor - Indrikis KRAMS, Janīna DAUKŠTE, Inese KIVLENIECE, Ants KAASIK, Tatjana KRAMA, Todd M. REEBERG, Markus J. RANTALA (Current Zoology, 2013)
Encapsulation is a nonspecific, cellular response through which insects defend themselves against multicellular pathogens. During this immune reaction, haemocytes recognize an object as foreign and cause other haemocytes to aggregate and form a capsule around the object, often consisting of melanized cells. The process of melanisation is accompanied by the formation of potentially toxic reactive oxygen species, which can kill not only pathogens but also host cells. In this study we tested whether the encapsulation response is costly in mealworm beetles Tenebrio molitor. We found a negative relationship between the duration of implantation via a nylon monofilament and remaining life span. We also found a negative relationship between the strength of immune response and remaining life span, suggesting that cellular immunity is costly in T. molitor, and that there is a trade-off between immune response and remaining life span. However, this relationship disappeared at 31-32 hours of implantation at 25 ± 2℃. As the disappearance of a relationship between duration of implantation and lifespan coincided with the highest values of encapsulation response, we concluded that the beetles stopped investment in the production of melanotic cells, as the implant, a synthetic parasite, was fully isolated from the host’s tissues [Current Zoology 59 (3): 340–346, 2013].